Assessment of the Application of Wind Power in Indonesia - Lilis Noviani (Indonesian Journal of Physics and Nuclear Applications, 2019)
Energy and the environment are major topics of concern throughout the world nowadays. Consumption of fossil fuels is still the dominance to meet energy needs. The adverse effects of the consumption of fossil fuels on the environment and humans are priorities in determining policies. Many countries in the world have begun restructuring their energy mix and exploring the potential of new and renewable energy (NRE). Indonesia is currently in a stage of economic development where the demand for energy consumption is extremly high. The availability of fossil fuel energy is decreasing and is expected to run out in the next 42 years. In addition, environmental pollution due to the use of fossil fuels continues to increase. The application of NRE technologies and better efficiency in energy’s use could help decrease dependence on fossil fuels. One of the energy’s commodities that warrants attention is wind energy. However, the development of wind power plants in Indonesia has many barriers. The low level of trust in wind availability and the high investment costs are the main barriers to its development. The current capacity of wind energy power plants in Indonesia installed is 1.96 MW, whereas the total amount of wind energy available in Indonesia is 970MW. Wind power plants produce less carbon. This makes wind power one of the solutions to have environmentally friendly power plants. This assessment aims to increase awareness for planning for the future with the collaboration of conventional energy and NRE as clean technology to save the world from global warming.